A review of localization techniques in breast surgery – is wire free the future? (2020)
In the UK the gold standard for localisation of impalpable breast lesions including cancers, is the image guided hook wire localiser and has been since its development in the 1970’s. Localisation methods have changed and advanced since this inception. The technique of wire localisation has both advantages and disadvantages. In recent years novel wire free techniques, using probe and marker/seed based systems, (e.g. Magseed®, SCOUT®, and LOCalizer™) have been developed to not only localise impalpable breast lesions but negate the disadvantages of wire localisation. The aim of our review was to compare the variety of techniques used to localise breast lesions from their origins to the most recent advancements. A comprehensive review of available data in the form of published articles with the related topic using Pubmed, OVID, Cochrane databases, book chapters and information from manufacturer’s websites. Key words used for database searches included impalpable breast tumours; localisation techniques; wire free technique; Magseed; SAVI SCOUT and LOCaliser. This was a narrative review comparing the disadvantages and advantages of each technique, wire based or wire free.